The Impact of Scaffolding Strategies Within the Zone of Proximal Development on Fourth-Grade Students’ Conceptual Understanding in Mathematics - Yuyun Yumiarty; Ummi Putri Sakina; Irni Latifa Irsal; Guntur Gunawan (STAI Hubbulwathan Duri, 2025)
Conceptual understanding in mathematics remains a persistent challenge for elementary students, particularly when instructional strategies fail to match their developmental needs. This study investigates the effectiveness of scaffolding strategies based on Vygotsky’s Zone of Proximal Development (ZPD) in enhancing fourth-grade students’ conceptual understanding in mathematics. A quasi-experimental design with a non-equivalent control group was employed, involving 52 fourth-grade students from MIN 03 Kepahiang. Participants were divided into two groups: one received instruction using ZPD-based scaffolding strategies, while the other experienced conventional teaching methods. Data were collected through validated descriptive pre- and post-tests and analyzed using paired sample t-tests and two-way ANOVA. The findings indicate that scaffolding strategies significantly improved students’ conceptual understanding compared to conventional methods (p 0.05). Students at the actual developmental level achieved higher scores (M = 75.15) than those at the potential level (M = 59.88). A significant interaction effect (p 0.05) was found between teaching strategy and ZPD level, suggesting that scaffolding is more effective for students at the potential development level, while conventional methods better support students at the actual level. The study supports the use of developmentally appropriate scaffolding to enhance mathematical understanding. However, limitations include the study’s short intervention duration and single-school setting. Future research should explore long-term effects, apply ZPD-based scaffolding across diverse contexts, and investigate the use of technology for dynamic ZPD assessment. These findings reinforce the need for tailored instruction in mathematics education.